Electrospinning and Its Applications in the Food Sector - , Ganga A; , Divyashree M; , Samit Dutta (Archives of Current Research International, 2025)
Electrospinning is an advanced nanotechnology-based technique that enables the fabrication of ultrafine fibers with unique physicochemical properties. In the food sector, electrospinning has emerged as a promising tool for encapsulating bioactive compounds, improving the stability and controlled release of nutrients, analysis of different food components, pesticides, antibiotics, production of different food packaging systems includes antibacterial packaging, antioxidant packaging and intelligent packaging. This technology allows for the development of biodegradable, functionalized, and nanostructured materials that can enhance food quality, safety, and shelf life. Additionally, electrospun nanofibers can be used to incorporate antimicrobial agents, probiotics, and flavour compounds, offering novel applications in food preservation and fortification. However, challenges related to scalability, regulatory approval, and material selection remain critical barriers to large-scale industrial adoption. This review provides a comprehensive overview of electrospinning principles, techniques, Factors affecting the process, and applications, highlighting its future prospects and limitations.